The Contribution of Organised Leisure-Time Activities in Shaping Positive Community Health Practices among 13-and 15-Year-Old Adolescents: Results from the Health Behaviours in School-Aged Children Study in Italy - Borraccino, Alberto; Lazzeri, Giacomo; Kakaa, Omar; Bad'ura, Petr; Bottigliengo, Daniele; Dalmasso, Paola; Lemma, Patrizia (International journal of environmental research and public health, 2020)
Background and Objective: Participation in organised out-of-school leisure-time activities (OLTAs) has been shown to have a positive impact on community health practices and to lessen inequities in social and environmental opportunities among youths. According to the social capital theory, OLTAs foster bridging ties that allow individuals to forge new, wider-ranging social connections, increasing social integration and opportunities for identity-related exploration. This study aimed to describe participation in different types of OLTAs and its association with perceived life satisfaction, physical activity, tobacco use, alcohol consumption, and drunkenness in a representative sample of youths. Methods: A representative sample of 11-, 13- and 15-year-old students (n = 47,799) was recruited throughout all Italian regions within the Italian 2013/2014 Health Behaviours in School-aged Children (HBSC) study. Data were collected according to the HBSC study protocol. Participants were compared on outcomes according to OLTA participation type (i.e., non-sport, sport-only, and mixed vs. no-OLTA). In accordance with the study sampling procedures, hierarchical logistic regression models were used. Results: Participation in OLTAs was significantly associated with high life satisfaction in all ages (sport-only: odds ratio (OR) = 1.67, 1.48 and 1.55 for 11- 13- and 15-year-olds; mixed: OR = 1.95, 1.60 and 1.45, respectively). Youths participating in OLTAs were more likely to meet physical activity recommendations and report lower rates of tobacco use and drunkenness. Conclusions: Participation in OLTAs showed a favourable impact on health behaviours. Thus, community organisations and clubs, whether supported by public investments, could contribute to the enhancement of beneficial health practices, by engaging and serving the community as a whole and further reducing inequities in both social and environmental opportunities.
Keywords: Italy; volnočasové aktivity; alcohol and tobacco use; physical activity recommendations; zdravé chování; lidé; mladiství; Public Health; školy; mužské pohlaví; life satisfaction; Schools; ženské pohlaví; Health Behavior; Humans; organized leisure-time activities (OLTA); Itálie; health practices; Female; veřejné zdravotnictví; Leisure Activities; Adolescent; HBSC; Male